Liver sharing and organ procurement organization performance under redistricted allocation. Issue 8 (August 2015) - Gentry, Sommer E.; Chow, Eric K. H.; Massie, Allan; Luo, Xun; Shteyn, Eugene; Pyke, Joshua; Zaun, David; Snyder, Jon J.; Israni, Ajay K.; Kasiske, Bert; Segev, Dorry L.
<x xml:space="preserve">Abstract</x> Concerns have been raised that optimized redistricting of liver allocation areas might have the unintended result of shifting livers from better‐performing to poorer‐performing organ procurement organizations (OPOs). We used liver simulated allocation modeling to simulate a 5‐year period of liver sharing within either 4 or 8 optimized districts. We investigated whether each OPO's net liver import under redistricting would be correlated with 2 OPO performance metrics (observed to expected liver yield and liver donor conversion ratio), along with 2 other potential correlates (eligible deaths and incident listings above a Model for End‐Stage Liver Disease score of 15). We found no evidence that livers would flow from better‐performing OPOs to poorer‐performing OPOs in either redistricting scenario. Instead, under these optimized redistricting plans, our simulations suggest that livers would flow from OPOs with more‐than‐expected eligible deaths toward those with fewer‐than‐expected eligible deaths and that livers would flow from OPOs with fewer‐than‐expected incident listings to those with more‐than‐expected incident listings; the latter is a pattern that is already established in the current allocation system. Redistricting liver distribution to reduce geographic inequity is expected to align liver allocation across the country with the distribution of supply and demand rather than transferring livers from better‐performing OPOs to poorer‐performing OPOs. Liver Transpl 21:1031‐1039, 2015. © 2015 AASLD.